Electrophysiological effects of intravitreal Avastin (bevacizumab) in the treatment of exudative age-related macular degeneration. Issue 9 (10th July 2008) - Karanjia, R; Eng, K T; Gale, J; Sharma, S; Hove, M W ten
Abstract : Objective: To examine the sensitivity of the multifocal electroretinogram (mf-ERG) at measuring changes in retinal electrical activity in response to Avastin (bevacizumab) treatment for age-related macular degeneration (ARMD). Methods: Nine subjects with exudative ARMD, not previously treated with bevacizumab in the investigated eye, underwent pretreatment testing with mf-ERG and intravenous fluorescein angiography (IVFA). A second mf-ERG test was conducted post-treatment. The P1 response amplitudes were examined for the hexagons corresponding to areas of pathology on the IVFA. Intertest variability was accounted for by examining areas without pathology. Aggregate responses were also generated for central and lesion-associated responses. Results: Changes in P1 response amplitude correlated with changes in visual acuity (R 2 >0.96). An improvement in Snellen visual acuity correlated with a significant improvement in P1 response amplitude from lesion associated recordings (p<0.03). Changes in P1 response amplitudes were not observed when aggregate responses were generated. Conclusion: This study represents a novel method for assessing an improvement of mf-ERG responses. This is the first study to demonstrate a statistically significant change in retinal electrical activity postbevacizumab in patients with ARMD. This study demonstrates a method for utilising mf-ERG to assess changes in retinal electrical activity and to assess the effectiveness of treatments such as bevacizumab.